Undergraduate Research Program to Recycle Composite Waste - Waleed Ahmed; Essam Zaneldin; Amged Al Hassan (MDPI AG, 2021)
With the rapid growth in the manufacturing industry and increased urbanization, higher amounts of composite material waste are being produced, causing severe threats to the environment. These environmental concerns, coupled with the fact that undergraduate students typically have minimal experience in research, have initiated the need at the UAE University to promote research among undergraduate students, leading to the development of a summer undergraduate research program. In this study, a recycling methodology is presented to test lab-fabricated Carbon-Fiber-Reinforced Polymer (CFRP) for potential applications in industrial composite waste. The work was conducted by two groups of undergraduate students at the UAE University. The methodology involved the chemical dissolution of the composite waste, followed by compression molding and adequate heat treatment for rapid curing of CFRP. Subsequently, the CFRP samples were divided into three groups based on their geometrical distinctions. The mechanical properties (i.e., modulus of elasticity and compressive strength) were determined through material testing, and the results were then compared with steel for prompt reference. The results revealed that the values of mechanical properties range from 2 to 4.3 GPa for the modulus of elasticity and from 203.7 to 301.5 MPa for the compressive strength. These values are considered competitive and optimal, and as such, carbon fiber waste can be used as an alternate material for various structural applications. The inconsistencies in the values are due to discrepancies in the procedure as a result of the lack of specialized equipment for handling CFRP waste material. The study concluded that the properties of CFRP composite prepreg scrap tend to be reusable instead of disposable. Despite the meager experimental discrepancies, test values and mechanical properties indicate that CFRP composite can be successfully used as a material for nonstructural applications.